Rhetoric in Ustadz Khalid Basalamah's Preaching Through Social Media - Jihan Fatmah (Aslama: Journal of Islamic Studies, 2024)
Rhetoric is the art of speaking that is quite influential in human life. Rhetoric has two models, namely monologue and dialogic. Monologic is a rhetorical model which means the art of speaking one way in front of the public. Monologue has special characteristics that are oriented towards providing information and reactions to the audience. Meanwhile, dialogic means the art of speaking in a dialogic or multi-directional manner. It has special characteristics that are oriented towards objective and democratic conclusions. However, it is not enough to just use the rhetorical model, the conversation delivered either monologue or dialogic must be structured. There are stages of message preparation that can be used to make it easier for the audience to receive the message delivered. There are two stages that can be used to compile a message, the first is organizing and the second is organizing the message. One person who has rhetorical skills in delivering lectures is Ustadz Khalid Basalamah. He has been consistent, since 2013 until now, to continue to deliver lectures on his personal Youtube account, Khalid Basalamah Official. The purpose of writing this article is to find out Rhetoric in Preaching Ustadz Kholid Basalamah. The method in this writing is to use qualitative research as an effort to explain the da'wah method used by the resource person in his da'wah. In this study, the author uses the content analysis research method or content analysis. The results of writing this article are that Khalid Basalamah is an example of a da'wah in Indonesia who has utilized communication technology in the form of social media, especially YouTube as a medium for conveying Islamic teachings. The majority of Khalid Basalamah's lectures based on the samples taken focus on faith, morals, and social messages of faith including repentance, piety, and the Day of Judgment. While the theme of worship includes the morals of patience and apologizing. The social theme includes helping each other.